Access to supportive care during and after cancer treatment and the impact of socioeconomic factors. (3rd October 2018) - Sharp, Lena; Westman, Bodil; Olofsson, Anna; Leppänen, Arja; Henriksson, Roger
Abstract: Background : Sweden's national cancer strategy points out several areas of cancer care that need improvements. Among them the need for supportive care resources to be accessible through the entire cancer trajectory and the reduction of socioeconomic inequalities. The aim of this study was to compare the patient-reported access to supportive care in the Stockholm-Gotland region between patients diagnosed in 2014 and 2016. The aim was also to describe how socioeconomic and other demographic factors impact access to supportive care. Material and methods: All patients with gynaecological, head and neck, haematological and upper gastrointestinal cancers diagnosed in the Stockholm-Gotland regions were identified through the Swedish Cancer Registries. Data were collected via a questionnaire on demographic, socioeconomic factors and patients' perception ( n = 1872) of access to supportive care. Data were summarized using descriptive statistics and logistic regression was used for relevant variables. Results: Access to some supportive care resources, such as contact nurses (CNs) and individual written care plans (IWCPs) had significantly improved from 2014 to 2016. The proportion of patients that had received information about patient advocacy groups (PAGs) had also improved but remained on a relatively low level (29 and 35%, respectively). The proportion of patients being refereed to palliative care (PC) did not change between 2014 and 2016. In total, 10% of the patients reported to having received information on second medical opinion (SMO). Patients that had undergone multimodality cancer treatment were more likely to report access to supportive care, and those with lower education levels were more likely to have access to CNs and IWCPs. Conclusion: Access to some of the supportive care resources have shown improvements in the Stockholm-Gotland region but further efforts are required, especially regarding access to PC, information about PAGs and SMOs.